(untitled) (Philological Studies, 2025)
The connections between Macedonian and Slavic literatures are more than literary. They have deep historical roots and common themes that are intertwined in language, folk tradition, art, culture and literature. This paper systematizes the academic interest of students at the Department of Slavic Studies, Faculty of Philology in Ljubljana, with a bibliographical and descriptive overview of the titles of undergraduate, master’s and doctoral theses defended at this department, which have authors and works from Macedonian literature. Interests in Macedonian literature has changed over time and these works have several development periods. The entire material goes towards revealing the thesis that literature reflects the deep historical, cultural and political connections that develop through different periods and contexts. The roots are recognized even in folklore and they reflect the connections between the peoples of the Slavic regions. Starting from language, script, tradition, to themes and forms of expression. The research interest, the choice of topics and authors, and the discovery of the common historical thread that connects Slovenian and Macedonian literature.